Análisis del sitio web de la Universidad Técnica de Babahoyo basado en rendimiento y usabilidad. - Preciado Contreras, Walter Daniel (2023)
This case study aims to provide a comprehensive evaluation of the Babahoyo Technical University website, focusing on performance and usability. The results and recommendations obtained will allow the implementation of concrete improvements that optimize the user experience, strengthen institutional communication and promote easy and efficient access to relevant information for the university community. The analysis was carried out using a combination of specialized techniques and tools that made it possible to evaluate the performance, accessibility, navigation and integration of social networks of the website. The results obtained will provide valuable information to identify areas for improvement and recommend specific actions to optimize the user experience. By carrying out this analysis in the context of the Technical University of Babahoyo, the aim is to improve the way in which users interact with the website. In addition, it seeks to ensure that the website complies with accessibility standards, thus guaranteeing the inclusion of all users.